2011
DOI: 10.1007/978-3-642-23985-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Discovery of Complementary Learning Resources

Abstract: Abstract. Students in a learning experience can be seen as a commu-nity working simultaneously (and in some cases collaboratively) in a set of activities. During these working sessions, students carry out nu-merous actions that affect their learning. But those actions happening outside a class or the Learning Management System cannot be easily observed. This paper presents a technique to widen the observability of these actions. The set of documents browsed by the students in a course was recorded during a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our findings that students' reporting about their self-efficacy and anxiety significantly contributed to their final exam results corroborated previous findings (Romero-Zaldivar et al, 2012;Joksimović et al, 2015). Similar to previous research (Pardo et al, 2016a,b), we also found that self-efficacy positively affected students' learning achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that students' reporting about their self-efficacy and anxiety significantly contributed to their final exam results corroborated previous findings (Romero-Zaldivar et al, 2012;Joksimović et al, 2015). Similar to previous research (Pardo et al, 2016a,b), we also found that self-efficacy positively affected students' learning achievement.…”
Section: Discussionsupporting
confidence: 92%
“…The events recorded with the browser offer a glimpse of the type of documents that students browse while working in the activities. A significant proportion of these documents will be part of the official course material, but there will be additional documents not part of the course but related to the topic (Romero-Zaldivar, Crespo García, Burgos, Delgado Kloos, Pardo, 2011). The collected events could be used in a crowd-sourcing approach to detect resources that are not included in the course material but are relevant to the topic.…”
Section: Future Workmentioning
confidence: 99%
“…Furthermore, they can be used as basis of recommender systems and for evaluating recommendation algorithms, as proposed by Verbert et al (2011). Such an application is reported by Romero Zaldívar et al (2011).…”
Section: Collected Datasetsmentioning
confidence: 99%